Analysis of The Commercial Court’s Decision on The Postponement of Debt Payment Obligations to Life Insurance Companies Without The Approval of The Financial Service Authority: Case Study Case Number 389/Pdt.Sus-PKPU/2020/PN Niaga Jkt. Pst - Amalia, Siti; Judge, Zulfikar (Ann Publisher, 2023)
The Financial Services Authority (hereinafter referred to as